Influence of climate changes on railway superstructure - Katarina Vranešić; Ivo Haladin; Krešimir Burnać (Građevinar)
Weather conditions significantly impact transportation systems, particularly in terms of safety, mobility, accessibility, economic efficiency, and infrastructure resilience. Currently, approximately 27 % of the world’s road and rail infrastructure is exposed to at least one type of damaging weather condition. The extent to which rail infrastructure is affected by climate change largely depends on its geographic location. Climate change poses a serious risk to rail transport, with the potential to disrupt operations or bring them to a complete standstill. This paper examines the effects of extreme weather conditions, including high and low temperatures, strong wind gusts, snow and ice, as well as flooding, on the superstructure of ballasted tracks. It also highlights measures that can mitigate the adverse impacts of climate change on railway infrastructure. Furthermore, it emphasizes the importance of regular track inspections, the adoption of advanced railway monitoring methods, and thorough track condition assessments following extreme weather events.